A Novel Inducible Mouse Model of MLL-ENL-driven Mixed-lineage Acute Leukemia. Issue 4 (August 2018) - Stavropoulou, Vaia; Almosailleakh, Marwa; Royo, Hélène; Spetz, Jean-François; Juge, Sabine; Brault, Laurent; Kopp, Patrick; Iacovino, Michelina; Kyba, Michael; Tzankov, Alexandar; Stadler, Michael B.; Cazzaniga, Gianni; et al.
Abstract : Abstract: Previous retroviral and knock-in approaches to model human t(11;19) + acute mixed-lineage leukemia in mice resulted in myeloproliferation and acute myeloid leukemia not fully recapitulating the human disease. The authors established a doxycycline (DOX)-inducible transgenic mouse model " iMLL-ENL " in which induction in long-term hematopoietic stem cells, lymphoid primed multipotent progenitor cells, multipotent progenitors (MPP4) but not in more committed myeloid granulocyte-macrophage progenitors led to a fully reversible acute leukemia expressing myeloid and B-cell markers. iMLL-ENL leukemic cells generally expressed lower MLL-ENL mRNA than those obtained after retroviral transduction. Disease induction was associated with iMLL-ENL levels exceeding the endogenous Mll1 at mRNA and protein levels. In leukemic cells from t(11;19) + leukemia patients, MLL-ENL mRNA also exceeded the endogenous MLL1 levels suggesting a critical threshold for transformation. Expression profiling of iMLL-ENL acute leukemia revealed gene signatures that segregated t(11;19) + leukemia patients from those without an MLL translocation. Importantly, B220 + iMLL-ENL leukemic cells showed a higher in vivo leukemia initiation potential than coexisting B220 − cells. Collectively, characterization of a novel transgenic mouse model indicates that the cell-of-origin and the fusion gene expression levels are both critical determinants for MLL-ENL -driven acute leukemia. Abstract : Supplemental Digital Content is available in the text